2013
DOI: 10.1016/j.coviro.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel vaccine strategies against emerging viruses

Abstract: One of the main public health concerns of emerging viruses is their potential introduction into and sustained circulation among populations of immunologically naïve, susceptible hosts. The induction of protective immunity through vaccination can be a powerful tool to prevent this concern by conferring protection to the population at risk. Conventional approaches to develop vaccines against emerging pathogens have significant limitations: lack of experimental tools for several emerging viruses of concern, poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Utilizing a truly validated animal model mimicking CHIKV infection in humans, we were able to address how these three different vaccine modalities compare head-tohead in terms of immunogenicity and protective efficacy. Previous studies of CHIKV vaccine candidates in smaller animals (mice) have shown that a large number of CHIKV vaccine candidates are able to provide protective immunity (6,(26)(27)(28). Thus, it was of importance to assess the individual merits of new CHIKV vaccine platforms in a more stringent animal model that more closely resembles a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing a truly validated animal model mimicking CHIKV infection in humans, we were able to address how these three different vaccine modalities compare head-tohead in terms of immunogenicity and protective efficacy. Previous studies of CHIKV vaccine candidates in smaller animals (mice) have shown that a large number of CHIKV vaccine candidates are able to provide protective immunity (6,(26)(27)(28). Thus, it was of importance to assess the individual merits of new CHIKV vaccine platforms in a more stringent animal model that more closely resembles a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Other efforts rely on computational and bioinformatic tools to identify highly conserved segments of antigenic genes or proteins and their binding epitopes (e.g., Conservatrix, EpiMatrix) . Well‐developed platforms can be modified for speedy use against novel viruses …”
Section: How Can We Defend Against Emerging Viruses?mentioning
confidence: 99%
“…Furthermore, DNA vaccines are not affected by anti-vector immunity [7] commonly associated to virus-based vectors used for vaccination. However it is also true that in some cases the development of DNA vaccines present limitations mainly associated to their intrinsic low immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…However it is also true that in some cases the development of DNA vaccines present limitations mainly associated to their intrinsic low immunogenicity. Consequently, research has been conducted to improve the immunogenicity of the vaccines by combining them with adjuvants, either co-administered with the vaccine or encoded in the same plasmid [7]. Up until today, different molecules of the innate immune system [8][9][10], ␤-glucans [11], poly I:C [12][13][14] and other strategies [15][16][17][18] have been used to improve DNA vaccination protection rates.…”
Section: Introductionmentioning
confidence: 99%